A novel multi-scale Hessian based spot enhancement filter for two dimensional gel electrophoresis images. (1st November 2015) - Shamekhi, Sina; Miran Baygi, Mohammad Hossein; Azarian, Bahareh; Gooya, Ali
Abstract: Two dimensional gel electrophoresis (2DGE) is a useful method for studying proteins in a wide variety of applications including identifying post-translation modification (PTM), biomarker discovery, and protein purification. Computerized segmentation and detection of the proteins are the two main processes that are carried out on the scanned image of the gel. Due to the complexities of 2DGE images and the presence of artifacts, the segmentation and detection of protein spots in these images are non-trivial, and involve supervised and time consuming processes. This paper introduces a new spot filter for enhancing, and separating the closely overlapping spots of protein in 2DGE images based on the multi-scale eigenvalue analysis of the image Hessian. Using a Gaussian spot model, we have derived closed form equations to compute the eigen components of the image Hessian of two overlapping spots in a multi-scale fashion. Based on this analysis, we have proposed a novel filter that suppresses the overlapping area and results in a better spot separation. The performance of the proposed filter has been evaluated on the synthetic and real 2DGE images. The comparison with three conventional techniques and a commercial software package reveals the superiority and effectiveness of the proposed filter. Abstract : Highlights: We introduce a novel spot filter for separating the closely overlapping protein spots. We compute the eigen components of the image Hessian of two overlapping spots. We evaluate the performance of the proposed filter on the synthetic and real images. Comparison with other methods and a commercial software package reveals the superior performance of the proposed filter.